Pelatihan Digital Model PERMA untuk Meningkatkan Career Wellbeing Guru Bimbingan dan Konseling di Pesisir Kabupaten Takalar - Syahril, M. Fiqri; Qarimah, Inayah Ridhayanti; Rizky, Alifia Ainun; Habulana, Andi Sitti Sahari; Qurani, Dita Putri (LESTARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
Guidance and Counseling (BK) teachers play an important role as students' psychological companions, yet their own career wellbeing is often overlooked, particularly among those serving in coastal areas with limited access to professional development. This community service program aimed to improve the career wellbeing of BK teachers affiliated with the Guidance and Counseling Teachers' Council (MGBK) of Takalar Regency through digital training based on the PERMA model (Positive Emotion, Engagement, Relationship, Meaning, Accomplishment). The activity was conducted at the hall of SMP Negeri 2 Takalar and was attended by 23 BK teachers. The implementation method consisted of a preparation stage, a digital training session combining lectures, discussions, and reflective practice on the five PERMA dimensions, and an evaluation using a pre-test and post-test design. The results showed that the career wellbeing score increased from 129 at pre-test to 139 at post-test, an increase of 10 points (7.75%). This improvement indicated a positive shift in teachers' perceptions of positive emotion, work engagement, professional relationships, meaningfulness of work, and career accomplishment. The findings provide preliminary evidence that PERMA-based digital training has the potential to strengthen BK teachers' career wellbeing and can serve as a basis for a more measurable and sustainable follow-up mentoring program within the Takalar Regency MGBK.